Highly conductive polymer with vertical phase separation for enhanced bioelectronic interfaces - Jiahuan Qiu; Yuyao Lu; Xinyuan Qian; Junxian Yao; Chengcan Han; Ziliang Wu; Hui Ye; Guorong Shan; Qiang Zheng; Kaichen Xu; Miao Du (npj Flexible Electronics)
Abstract Conductive polymers like poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT: PSS) are key materials in bioelectronics, but balancing ultrahigh conductivity with long-term tissue contact stability remains a challenge. Here, we present a solvent-mediated solid-liquid interface doping strategy to engineer vertically phase-separated (VPS) PEDOT: PSS films. By adjusting thickness and doping solvents, a thicker PEDOT: PSS film with a strong VPS structure was achieved, featuring a higher PSS/PEDOT ratio on the surface and a lower ratio at the bottom. Doping the pristine film with a metastable liquid-liquid contact solution enables gradual PSS migration and a significant component gradient, yielding films with a hydrophilic surface and one of the highest reported conductivities ( ~ 8800 S cm−1) for bioelectronic devices. The films patterned by laser processing present high-fidelity signal acquisition, and excellent electrochemical stability. With low impedance and long-term biocompatibility, they are employed for real-time wearable and implantable sensors for electrophysiological monitoring, showcasing broad potentials in bioelectronics and human–machine interactions.